(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Fractures of the distal tibia are unique in that the bone is subcutaneous with poor muscular coverage. The consequence of its decreased vascularity leads to complications like delayed bone union, wound complications such as dehiscence and infection. These fractures can be managed with various techniques. Open reduction and internal fixation by plating, have been used with varying results. In current orthopedic practice, minimally invasive percutaneous plating osteosynthesis (MIPO) and interlocking nailing are the preferred techniques for fractures of the distal third tibia. In our study, twenty adult patients with closed fractures of distal tibia were treated with LCP using MIPO technique & were followed for a period of one year (January 2014 to December 2014). Average age of patients studied was 40.5 years (18-55) with majority being high energy trauma (65% vs. 35%). Mean duration for surgery from day of identification to go for surgery was 4-7 days. Results were evaluated clinically and radiologically. In 18 cases (90%) fractures united & 2 cases (10%) had delayed union. All fractures were united by 20 weeks. Superficial skin infection was found in 2 cases, Valgus mal-alignment in 2 cases &1 case had ankle stiffness. Finally results showed:10 cases (50%) had excellent outcome, 4 cases (20%) had good outcome, 4 cases (20%) had fair outcome, and 2 cases (10%) had poor outcome. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):09-13